Serum Levels of Adipocyte Fatty Acid-Binding Protein Are Associated with the Severity of Coronary Artery Disease in Chinese Women - Bao, Yuqian (Public Library of Science, 2011)
BACKGROUND: Adipocyte fatty acid-binding protein (A-FABP) has been described as a novel adipokine, playing an important role in the development of metabolic syndrome, type 2 diabetes and atherosclerosis. In this study, we investigated the relationship between serum levels of A-FABP and the presence and severity of coronary artery disease (CAD) in Chinese subjects. METHODOLOGY/PRINCIPAL FINDINGS: Circulating A-FABP level was determined by ELISA in 341 Chinese subjects (221 men, 120 women) who underwent coronary angiography. A-FABP levels in patients with CAD were significantly higher compared with non-CAD subjects (P = 0.029 in men; P = 0.031 in women). Serum A-FABP increased significantly in multi-vessel diseased patients than in non-CAD subjects (P = 0.011 in men, P = 0.004 in women), and showed an independent correlation with coronary atherosclerosis index (standardized β = 0.173, P = 0.025). In multiple logistic regression analysis, serum A-FABP was an independent risk factor for CAD in women (OR = 5.637, 95%CI: 1.299-24.457, P = 0.021). In addition, amino terminal pro-brain natriuretic peptide (NT-proBNP) was demonstrated to be positively and independently correlated with A-FABP (standardized β = 0.135, P = 0.027). CONCLUSIONS/SIGNIFICANCE: Serum A-FABP is closely associated with the presence and severity of CAD in Chinese women.